(untitled) (Bangladesh Journal of Child Health, 2021)
Background: Constipation is not uncommon in childhood. This study was aimed to evaluate demography and probable/potential risk factors for functional constipation in Bangladeshi children. Materials & Method: This cross-sectional study was carried out among 179 children from May 2018 to June 2019 in the department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka both indoor and outdoor basis. Collected data from children with constipation who fulfilled the Rome III criteria were analyzed by SPSS 20. Results: Among 179 children, 54.75% were boys, and 45.25% girls. It was found more in age group above 5 years (56.42%), then in 2 to 5 years (33.52%) and lower in below 2 years (10.6%). Constipation was more in urban areas (55.3%) than in rural (44.69%). Among potential risk factors, low fiber in diet (72.63%) was most common, other factors were ingestion of cow’s milk (32.96%), not having regular meals with parents (19.55%), consumption of junk foods (28.49%), Staying with grandparents (16.76%), living in hostel or madrasa / residential, religious institute (5.03%), long period of academic activity (7.26%), unhygienic toilet in school (6.14%) were also found to be probable risk factors in this study. Conclusion: Functional constipation was found more in boys & above five-year age groups. Low dietary fiber, consumption of cow’s milk & junk food, unwillingness to use toilets in school were found as potential underlying risk factors of constipation. Bangladesh J Child Health 2020; VOL 44 (3) :148-152